Humanizing AI in Higher Education: Rethinking HR, Ethics, and Skill Development for University Employees in the SDG Era - Shreeja, Nair; Kritika, Banka; Ankur, Pandya (INTI International University, 2025)
The rapid integration of Artificial Intelligence (AI) in higher education presents a profound dilemma of how universities can balance technological innovation with ethical governance and sustainable human resource (HR) practices. This study addresses the ethical considerations in AI adoption, the lack of accountability and transparency in AI-assisted HR functions, and the skills gaps among university employees transitioning to an AI-supportive environment. Equity, bias, and preparedness are central to institutional integrity and employee wellness in digitally transforming traditional higher education organizations. This qualitative study employed semi-structured interviews with academic heads, human resource managers, and administrators, supported by a review of institutional policies, accreditation models, and AI governance reports. It sought to understand how universities are redefining their HR, ethics, and capacity building processes to integrate AI humanely in academic and operational spaces. The results identified three predominant themes: (1) unbalanced ethical frameworks and low transparency in AI-driven hiring and performance appraisal; (2) faculty and staff apprehension due to algorithmic biases, data privacy issues, and a lack of institutional oversight; and (3) an urgent need to develop emotional intelligence, interdisciplinary thinking, and digital sensitivity among employees. Based on these findings, the paper proposes a Humanizing AI in Higher Education Framework focusing on ethical accountability, diversified HR policies, and continuous professional learning, aligned with the United Nations Sustainable Development Goals (SDG 4 - Quality Education, SDG 8 - Decent Work, and SDG 16 - Peace, Justice, and Strong Institutions). This model offers strategies for universities to balance technological advancement with human values in the AI revolution